The Effect of Fiber Layer Orientation on the Properties of Hybrid Kenaf/Fiberglass Polyester Matrix Composite - Nurul Fazlin, Adnan; Nurjannah, Salim; Nurul Huda, Abu Bakar; Rasidi, Roslan; Siti Noorbaini, Sarmin; Mohamad Hafiz, Mohamad Kassim; Mohd Hazim, Mohamad Amini (Trans Tech Publications, 2024)
A hybrid composite is a combination of two or more reinforced in a matrix. Hybrid composite will give better properties as compared to individual fiber-reinforced polymer composites. This research aims to study the effect of different fiber layer orientations on the properties of hybrid kenaf/fiberglass polyester matrix composite. Two types of the composite were produced which are Sample 1, the fiber layer orientation is fiberglass, kenaf fiber, kenaf fiber and fiberglass (FG-K-K-FG), and Sample 2, the fiber layer orientation is fiberglass, kenaf fiber, fiberglass, and kenaf fiber (FG-K-FG-K). The composite is manufactured using the hand lay-up technique and hot pressed. 50 g of unsaturated polyester resin and 12 g of hardener, Methyl Ethyl Ketone Peroxide (MEKP) were mixed and applied on top of every layer of fiber before being compressed at 100°C for 10 minutes. The properties of the hybrid composite were determined by completing five types of tests which are tensile test, impact test, water absorption test, thermogravimetric analysis (TGA), and scanning electron microscope (SEM). The results showed that Sample 2 (FG-K-FG-K) has higher tensile strength compared to Sample 1 (FG-K-K-FG) with the value of 30.97 MPa and 0.23 MPa respectively. For the water absorption test, Sample 1 (FG-K-K-FG) with a value of 239.21% has the highest water absorption properties compared to Sample 2 (FG-K-FG-K) with a value of 180.22%. Samples 1 and 2 have no obvious differences in terms of their thermal stability characteristics for the TGA test. For SEM, it is observed that both samples showed an attachment of adhesive between fiber layers and matrix. The overall conclusion is Sample 2 (FG-K-FG-K) has high mechanical properties but needs improvement for low water absorption.